Pharmaceutical Prospects of Curcuminoids for the Remedy of COVID-19: Truth or Myth - Fu, Yaw-Syan; Ho, Wan-Yi; Kang, Ning; Tsai, May-Jywan; Wu, Jingyi; Huang, Liyue; Weng, Ching-Feng (Frontiers in Pharmacology, 2022)
Coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which is a positive-strand RNA virus, and has rapidly spread worldwide as a pandemic. The vaccines, repurposed drugs, and specific treatments have led to a surge of novel therapies and guidelines nowadays; however, the epidemic of COVID-19 is not yet fully combated and is still in a vital crisis. In repositioning drugs, natural products are gaining attention because of the large therapeutic window and potent antiviral, immunomodulatory, anti-inflammatory, and antioxidant properties. Of note, the predominant curcumoid extracted from turmeric (Curcuma longa L.) including phenolic curcumin influences multiple signaling pathways and has demonstrated to possess anti-inflammatory, antioxidant, antimicrobial, hypoglycemic, wound healing, chemopreventive, chemosensitizing, and radiosensitizing spectrums. In this review, all pieces of current information related to curcumin-used for the treatment and prevention of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection through in vitro, in vivo, and in silico studies, clinical trials, and new formulation designs are retrieved to re-evaluate the applications based on the pharmaceutical efficacy of clinical therapy and to provide deep insights into knowledge and strategy about the curcumin’s role as an immune booster, inflammatory modulator, and therapeutic agent against COVID-19. Moreover, this study will also afford a favorable application or approach with evidence based on the drug discovery and development, pharmacology, functional foods, and nutraceuticals for effectively fighting the COVID-19 pandemic.